Mechanisms and management considerations of parent-chosen feeding approaches to infants with swallowing difficulties: an observational study - Sudarshan R. Jadcherla (Nature Portfolio, 2021)
Abstract Videofluoroscopy swallow studies (VFSS) and high-resolution manometry (HRM) methods complement to ascertain mechanisms of infant feeding difficulties. We hypothesized that: (a) an integrated approach (study: parent-preferred feeding therapy based on VFSS and HRM) is superior to the standard-of-care (control: provider-prescribed feeding therapy based on VFSS), and (b) motility characteristics are distinct in infants with penetration or aspiration defined as penetration-aspiration scale (PAS) score ≥ 2. Feeding therapies were nipple flow, fluid thickness, or no modification. Clinical outcomes were oral-feeding success (primary), length of hospital stay and growth velocity. Basal and adaptive HRM motility characteristics were analyzed for study infants. Oral feeding success was 85% [76–94%] in study (N = 60) vs. 63% [50–77%] in control (N = 49), p = 0.008. Hospital-stay and growth velocity did not differ between approaches or PAS ≥ 2 (all P > 0.05). In study infants with PAS ≥ 2, motility metrics differed for increased deglutition apnea during interphase (p = 0.02), symptoms with pharyngeal stimulation (p = 0.02) and decreased distal esophageal contractility (p = 0.004) with barium. In conclusion, an integrated approach with parent-preferred therapy based on mechanistic understanding of VFSS and HRM metrics improves oral feeding outcomes despite the evidence of penetration or aspiration. Implementation of new knowledge of physiology of swallowing and airway protection may be contributory to our findings.